2019
DOI: 10.5152/tjsm.2019.116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Sport Injury Anxiety Scale to Turkish: Validity and Reliability Study

Abstract: The aim of this study is to adapt the "Sport Injury Anxiety Scale" (SIAS) developed by Rex and Metzler (2016) to the Turkish language, and to test the validity and reliability of the adapted version. Material and Methods: The original form of SIAS consists of 21 items and seven subscales, and it is a five-point Likert-type scale (1: strongly disagree, 2: disagree, 3: neutral, 4: agree, 5: strongly agree). The sub-scales are: Loss of Athleticism, Being Perceived as Weak, Experiencing Pain, Letting Down Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It includes 6 sub-dimensions: loss of athleticism, being perceived as weak, experiencing pain, letting down important others, re-injury, loss of social support. The SIAS, adapted into Turkish by Caz et al (2019), measures sports injury anxiety between 19 and 95 points. As the total or average score obtained from the 6 sub-dimension increases, the sport injury anxiety increases.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes 6 sub-dimensions: loss of athleticism, being perceived as weak, experiencing pain, letting down important others, re-injury, loss of social support. The SIAS, adapted into Turkish by Caz et al (2019), measures sports injury anxiety between 19 and 95 points. As the total or average score obtained from the 6 sub-dimension increases, the sport injury anxiety increases.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…This is also the first study to examine the relationship between injury characteristics and anxiety in dancers according to body regions. In the study in which the Sports Injury Anxiety Scale was adapted into Turkish, it was shown that the average anxiety score of the athletes was 14.69 (Caz et al, 2019). In studies conducted with dancers, concerns were calculated over the percentages of the participants (Jacobs et al, 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…The Cronbach's alpha internal consistency coefficient for the Sports Injury Anxiety Scale was found at 0.870. 14…”
Section: Athlete Information Formmentioning
confidence: 99%
“…13 Anxiety is expressed as a situation of fear and tension that can be observed frequently in the daily behavior of individuals, negatively affecting the athlete's performance. 5,14 Although some researchers have indicated that athletes with high level of anxiety are more likely to suffer more severe injuries than athletes with lower levels, others have shown no association between sports injury and anxiety. 15,16 In the prevention of injuries, it is important to determine psychological conditions along with indi-vidual and environmental protective measures and to the best of our knowledge, the lack of enough study was seen on the sports injury anxiety scale in wrestlers.…”
mentioning
confidence: 99%